The Concept of Qailulah (Midday Napping) from Neuroscientific and Islamic Perspectives - Tumiran, Mohd Amzari; Rahman, Noor Naemah Abdul; Saat, Rohaida Mohd; Kabir, Nurul; Zulkifli, Mohd Yakub; Hasan Adli, Durriyyah Sharifah (Springer, 2018)
Napping/siesta during the day is a phenomenon, which is widely practised in the world. However, the timing, frequency, and duration may vary. The basis of napping is also diverse, but it is mainly done for improvement in alertness and general well-being. Neuroscience reveals that midday napping improves memory, enhances alertness, boosts wakefulness and performance, and recovers certain qualities of lost night sleep. Interestingly, Islam, the religion of the Muslims, advocates midday napping primarily because it was a practice preferred by Prophet Muhammad (pbuh). The objectives of this review were to investigate and compare identical key points on focused topic from both neuroscientific and Islamic perspectives and make recommendations for future researches.